2015
DOI: 10.1016/j.procir.2015.08.074
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Feed Drilling of Carbon Fiber-Reinforced Thermoplastics

Abstract: Carbon fiber-reinforced thermoplastics (CFRTP) are just beginning to be utilized for various applications such as aerospace, automobiles, and sporting goods in place of CFRPs, and the demand for through-hole drilling of CFRTPs is increasing. In this study, the machinability in drilling of CFRTPs under various conditions was experimentally analyzed in terms of the material properties, and a feasibility study of ultrafast feed drilling was conducted. The results showed that delamination at the outlet surface can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…Inside conventional processes, such as drilling or milling, wear caused to the cutting edges increases the final costs and reduces the efficiency of these processes. Processes such as milling generate a smooth and clean surface with Rz values close to 9 µm and Ra values close to 2 µm [12,13]. This is in line with the results obtained in the conventional machining of thermoset composite materials, where results below 3.2 µm are required due to aeronautical tolerances [14].…”
Section: Introductionsupporting
confidence: 85%
See 2 more Smart Citations
“…Inside conventional processes, such as drilling or milling, wear caused to the cutting edges increases the final costs and reduces the efficiency of these processes. Processes such as milling generate a smooth and clean surface with Rz values close to 9 µm and Ra values close to 2 µm [12,13]. This is in line with the results obtained in the conventional machining of thermoset composite materials, where results below 3.2 µm are required due to aeronautical tolerances [14].…”
Section: Introductionsupporting
confidence: 85%
“…In contrast, the travel speed seems to have a more prominent effect in this configuration due to the dispersion of the water jet. When the jet starts machining at a very high speed and the first material (Steel) has a worse machinability, an excessive delay is generated between the machining of this and the second material (CFRTP) and an increase in the hydraulic pressure enhances the penetration capacity of the water jet improving the surface integrity in spite of obtaining very high Ra values [13]. On the other hand, the results obtained in steel machining in terms of Ra ( Figure 16) and Rz (Figure 17) are very close to those obtained in the reverse configuration.…”
Section: Steel/cfrtpmentioning
confidence: 99%
See 1 more Smart Citation
“…DeFu Liu et al [21] reviewed on mechanical drilling of composite materials; including drilling operations, geometry and materials of drill bit, drilling-induced delamination, thrust force, wear of tools, delamination reduction approaches and certain marked characteristics during the fiber metal laminates (FML) drilling. Yasuhiro Kakinuma et al [22] recommended ultrafast feed drilling (UFFD) to obtain holes in Carbon fiber reinforced thermoplastics sheet with thermoplastic binding. The validity of the study was confirmed by experimental comparison of ultrasonic vibration-assisted drilling (UVD) and abrasive water jet machining (AWJ).…”
Section: Introductionmentioning
confidence: 99%